Enhanced ionisation of polyatomic molecules in intense laser pulses is due to energy upshift and field coupling of multiple orbitals - Erattupuzha, Sonia; Covington, Cody L.; Russakoff, Arthur; Lotstedt, Erik; Larimian, Seyedreza; Hanus, Vaclav; Bubin, Sergiy; Koch, Markus; Gräfe, Stefanie; Baltuska, Andrius; Xie, Xinhua; Yamanouchi, Kaoru; et al. (Journal of Physics B-Atomic Molecular and Optical Physics, 2017)
We present the results of a combined experimental and numerical study on strong-field ionisation of acetylene performed with the aim of identifying the mechanism behind the previously reported surprisingly large multi-electron ionisation probabilities of polyatomic molecules. Using coincidence momentum imaging techniques and time-dependent density functional simulations, we show that the reported efficient ionisation is due to the combined action of a significant geometrically induced energy upshift of the most relevant valence orbitals as the C-H distance stretches beyond about two times the equilibrium distance, and a strong increase in the coupling between multiple molecular orbitals concomitant with this stretch motion. The identified enhanced ionisation mechanism, which we refer to as EIC-MOUSE, is only effective for molecules aligned close to parallel to the laser polarisation direction, and is inhibited for perpendicularly aligned molecules because of a suppression of the C-H stretch motion during the onset of ionisation.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Coupling of multiple orbitals; enhanced ionisation; multiple ionisation and fragmentation of polyatomic molecules